Avoidance of Possible Collisions of Mobile Robots - Bartkevičius, S.; Jakas, Ž.; Šarkauskas, K. (Elektronika ir Elektrotechnika, 2010)
Known environment is moving more than one mobile robot to a certain point in time to confront the inevitable conflict between ro-bots and the more robots in one room collisions increases. Possible solution to the conflict – preconflict rules, movement correction, introduction. Correction carried out in a virtual time, so all the movement trajectory of the robot, taking into account all possible colli-sions, are counted against before transfer of the movement paths to the robots.